Assessment of the Role of Health Education in the Prevention of Coronavirus (COVID-19) Infection among Public Secondary School Students in Lokoja Metropolis, Kogi State, Nigeria - Adeola, Moses Folusayo; Eze, Dorothy Nwakaego (International Journal of Human Kinetics, Health and Education, 2022)
The study assessed the role of health education in the prevention of Coronavirus (COVID-19) among secondary school students in Lokoja metropolis of Kogi State, Nigeria. The study adopted descriptive survey research design. Purposive and simple random sampling techniques were used to select two hundred (200) respondents. Data were collected using a self structured questionnaire with Cronbach’s Alpha reliability index of 0.71. Descriptive statistics of mean and standard deviation and inferential statistics of t-test were used for data analysis. The results revealed that health education plays significant role in the prevention of COVID-19 infection through the provision of adequate knowledge on Covid-19 preventive measures. The study concluded that health education helped in effectively preventing the spread of Covid-19 infection among secondary school students in Kogi state through provision of adequate information on COVID-19 preventive measures and creating awareness on the need to adhere to the preventive measures on COVID-19. However, schools should collaborate with appropriate health authorities and organizations in promoting Covid-19 awareness particularly in secondary schools.